Intermittent post-exercise sauna bathing improves markers of exercise capacity in hot and temperate conditions in trained middle-distance runners - Kirby, N. V. N.; Lucas, S. J. E.; Armstrong, O. J.; Weaver, S. R.; Lucas, R. A. I. (European Journal of Applied Physiology, 2021)
Purpose: This study investigated whether intermittent post-exercise sauna bathing across three-weeks endurance training improves exercise heat tolerance and exercise performance markers in temperate conditions, compared to endurance training alone. The subsidiary aim was to determine whether exercise-heat tolerance would further improve following 7-Weeks post-exercise sauna bathing. Methods: Twenty middle-distance runners (13 female; mean ± SD, age 20 ± 2 years, VO2max 56.1 ± 8.7 ml kg-1 min-1) performed a running heat tolerance test (30-min, 9 km h-1/2% gradient, 40 °C/40%RH; HTT) and temperate (18 °C) exercise tests (maximal aerobic capacity [VO2max], speed at 4 mmol L-1 blood lactate concentration ([La-]) before (Pre) and following three-weeks (3-Weeks) normal training (CON; n = 8) or normal training with 28 ± 2 min post-exercise sauna bathing (101-108 °C, 5-10%RH) 3 ± 1 times per week (SAUNA; n = 12). Changes from Pre to 3-Weeks were compared between-groups using an analysis of co-variance. Six SAUNA participants continued the intervention for 7 weeks, completing an additional HTT (7-Weeks; data compared using a one-way repeated-measures analysis of variance). Results: During the HTT, SAUNA reduced peak rectal temperature (Trec; - 0.2 °C), skin temperature (- 0.8 °C), and heart rate (- 11 beats min-1) more than CON at 3-Weeks compared to Pre (all p < 0.05). SAUNA also improved VO2max (+ 0.27 L-1 min-1; p = 0.02) and speed at 4 mmol L-1 [La-] (+ 0.6 km h-1; p = 0.01) more than CON at 3-Weeks compared to Pre. Only peak Trec (- 0.1 °C; p = 0.03 decreased further from 3-Weeks to 7-Weeks in SAUNA (other physiological variables p > 0.05). Conclusions: Three-weeks post-exercise sauna bathing is an effective and pragmatic method of heat acclimation, and an effective ergogenic aid. Extending the intervention to seven weeks only marginally improved Trec.